Chronic Conditions and Resilience: Adolescent Health Behaviors in the Midst of the COVID-19 Pandemic in Thailand - Phatchara Thitamethee MD; Narueporn Likhitweerawong MD, PhD; Orawan Louthrenoo MD; Nonglak Boonchooduang MD (SAGE Publishing, 2024)
Objective . To assess the impact of chronic illnesses on risk behaviors and psychosocial adjustments among adolescents during the COVID-19 pandemic in Thailand. Methods . A cross-sectional study was conducted between June 2021 and September 2022, including adolescents aged 10 to 18 years. Participants completed the Thai Youth Risk Behavior Survey and the Strengths and Difficulties Questionnaire (SDQ). Data were analyzed using descriptive statistics, Student's t -test, Chi-square test, and logistic regression. Results . Adolescents with chronic illnesses (n = 120) were more likely to exhibit risk behaviors related to violence (38.3%) and mental health issues (18.3%). They also scored higher on total difficulties (mean = 12.23, SD = 5.14) and emotional symptoms (mean = 3.08, SD = 2.45) than the healthy group (n = 120). Conclusion . During the COVID-19 pandemic, adolescents with chronic illnesses in Thailand demonstrated increased risk behaviors related to violence and mental health issues, highlighting the need for tailored interventions.